Beyond the career break : women returners' perceptions of the skills they bring from the home and barriers to their return to and advancement in paid work : an exploratory analysis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Human Resource Management at Massey University - Mason, Ruth (Massey University, 2000)
This thesis reports the results of a study about the perceptions of women who have returned to work after taking a career break due to family responsibilities (women returners). Most of the women who participated in the study believed that their career breaks and ongoing family commitments had adversely affected their careers. The participants also believed that, because of the skills they had acquired through their roles as caregivers and home managers, they were better employees. However, not all of the women valued those skills themselves, and many believed that their employers did not recognise them either. The study also found that women returners have various needs that, if not met, become barriers to their ability to be involved in paid work. The two most commonly reported needs were reduced hours and flexi-time. Good quality and affordable childcare, understanding from managers and colleagues, and a change in societal attitudes that equate time spent at work with ability and commitment were also important needs of women returners. Conclusions that arose suggest that employers should change policies and train managers and those involved in the recruitment and selection process to meet the needs of women returners. This will increase the organisation's ability to develop creative solutions that will support the needs of both the organisation and its employees. Furthermore, the government needs to consider the implementation of paid parental leave and allowing all childcare expenses to be claimed against earnings. Through implementing these suggestions, mothers will have more choice about when they return to work, allowing them to better meet their own needs as well as those of their families.
Keywords: Women; Employment re-entry; New Zealand